Publications in pediatric critical care medicine: trends from Pakistan - Qalab Abbas; Shahzad, Muhammad; Ur Rehman, Naveed; Cheema, Zahra; Ahmed, Abdul Rahim; Ul Haque, Anwar (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse the characteristics of research published from Pakistan on paediatric critical care medicine. Method: The exploratory study was conducted at the Aga Khan University, Karachi from July 2021 to March 2022, and comprised a comprehensive search on MedLine, Google Scholar and PakMediNet databases for literature from Pakistan pertaining to paediatric critical care medicine published between January 2010 and December 2021. The search was done using appropriate key words. Conference abstracts and papers authored by paediatric intensivists with unrelated topics were excluded. Data was extracted on a structured spreadsheet, and was subjected to bibliometric analysis. Data was analysed using SPSS 20. Results: Of the 7,514 studies identified, 146(1.94%) were analysed. These were published in 51 journals with a frequency of 13.3 per year. There were 107(73.3%) original articles, 96(65.8%) were published in PubMed-indexed journals, and 35(24%) were published in locally indexed journals. Further, 100(69.4%) papers were published from 5 paediatric intensive care units in Karachi, and 81(56%) were contributed by a single private-sector hospital. The total citation count was 1072, with 2(1.4%) papers receiving >50 citations. There was a linear trend with some skewing and an annual growth rate of >15%. Conclusion: Publications from Pakistan related to paediatric critical care medicine showed positive linear growth. There was a paucity of multicentre studies, randomised controlled trials, and high-impact publications. Key Words: Bibliometric analysis, Paediatric critical care medicine, Publications, Pakistan, Research.